Approaches to Upgrading Strategies of Attracting Highly-Technological Companies to Preferential Zones of the Tula Region - A. D. Zhukovskii (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
Social and economic development of Russian regions is an important component of economic policy of the Russian state. In view of this approach systematic elaboration of innovation mechanisms aiming at the development of highly-technological companies, especially in preferential zones of industrial and manufacturing type plays a profound role in national economy. The goal of the present research is to identify innovation approaches to upgrade strategies of attracting highly-technological companies to preferential zones of the Tula region and on the basis of obtained results to raise competitiveness of the region on home and international market. The key objective of the research is to improve theoretical and methodological support of the process of finding and registering factors and conditions for highly-technological companies’ location in the region on the basis of innovative organizational and economic mechanisms. In the research methods of systematic analysis, elements of process, effective and resource approaches were used, as well as advanced methods of collecting and processing initial information. In the Tula region since 2016 the government of the Russian Federation has initiated setting-up of three preferential zones: OEZ PPT ‘Uzlovaya’, TOR ‘Efremov’ and TOR ‘Alexin’ and the industrial park ‘Uzlovaya’. Thanks to tools of state support on the federal and regional level in the Tula region a unique and economically promising site for attracting highly-technological companies was created by having built highly-qualified new industries, which can provide a serious impulse for social and economic development and higher quality of life in the region.